Hodgkinâs disease in children: Experience of Radio-therapy Department CHU HASSAN II Fez - GHAMMAD, S.; ALLOUCHE, F.; TERRAB, FZ.; HASSANI, G. CHEBIHI; BOUHAFA, T.; ALAMI, Z.; HASSOUNI, K. (Journal of Medical Biomedical and Applied Sciences, 2018)
Hodgkin lymphoma is a type of malignant disorder in which Reed-Sterberg cells are present in a characteristicbackground of reactive inflammatory cells of various types, accompanied by fibrosis of variable degree.More than sixty years ago Hodgkinâs Lymphoma was considered a âsystemicâ malignancy and universally fatal. Morerecently less extensive radiation therapy in combination with chemotherapy has resulted in an excellent overall survivaland prolonged disease free survival in children.There is age specific difference in the representation of the various subtypes of Hodgkin lymphoma (lymphocyticpredominance 2â7% in adults and only 20% in children).